(untitled) (Research, Society and Development, 2022)
Introduction: Hospital infection is a public health risk, being responsible for the highest number of complications and deaths of hospitalized patients. The Hospital Infection Control Commission (CCIH) is therefore responsible for contributing with measures and actions to prevent and control infections and resistant bacteria. According to Resolution No. 300/97 of the Federal Council of Pharmacy, it is mandatory for the pharmacist to participate in this commission, contributing to important decision-making and being the essential professional among the others who are part of the commission. Objective: The present study aims to identify and highlight the role of pharmacists in controlling nosocomial infections and highlight their contribution to prevention. Methodology: The type of study was an Integrative Literature Review, with a descriptive, qualitative and quantitative approach, in which the databases available in the virtual libraries, SciELO, LILACS, BVS and PubMed, available in the years 2015 to 2021, were used. Result: Twelve articles were identified, which matched the proposed theme, as well as the proposed title. Thus, it is possible to analyze that the pharmacist plays an important role within the hospital pharmacy, contributing to safer prescribing and dispensing, standardization of antibiotics and germicides, educational measures to promote the rational use of medicines and the elaboration of therapeutic guides for dilution and reaction. adverse. Conclusion: Thus, pharmacists as a professional working in the CCIH effectively contribute to the reduction of hospital infectious cases.